Enhancing Academic Supervision of Madrasah Principals through Lesson Study Initiatives - Ninik Supriyati; Baharuddin Baharuddin; Sutiah Sutiah (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the utilization of Lesson Study as a medium for academic supervision by the Head of MTs Negeri Rejoso, focusing on its role in improving teaching quality and fostering professional development among educators. A qualitative case study approach was adopted, employing data collection methods such as observation, interviews, and document analysis. These techniques provided comprehensive insights into the implementation and outcomes of Lesson Study activities in the madrasah context. The findings reveal that the Lesson Study is an effective academic supervision tool utilized by the Head of Madrasah. Key patterns of its application include collaborative lesson planning, classroom observation, and reflective discussions. This approach enables the Head of Madrasah to engage with teaching processes directly, identify teacher strengths and areas for improvement, and offer constructive feedback. Furthermore, Lesson Study fosters a collaborative culture, enhances teacher ownership of instructional practices, and strengthens involvement in continuous professional development initiatives. These findings emphasize the potential of Lesson Study to transform supervisory practices in educational settings. By integrating collaboration and active participation, Lesson Study supports the development of a shared commitment to improving teaching quality. The approach aligns with the goals of participatory supervision, enhancing both individual teacher performance and collective educational outcomes. Lesson Study serves as a sustainable and impactful medium for academic supervision in madrasahs. Future initiatives should focus on expanding its application and exploring its long-term effects on professional development and educational quality improvement.